1984
DOI: 10.1084/jem.159.5.1502
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of a cross-reactive idiotype on human autoantibodies with antibody against a synthetic peptide.

Abstract: The molecular basis of immunoglobulin idiotypes (1) has been pursued in several well-defined antibody systems (2-7). The accumulated results have suggested that the hypervariable regions (complementarity-determining regions, CDR) 1 of the light and heavy polypeptide chains usually contribute to the formation of idiotypic determinants. In the extensively analyzed murine antidextran model, one private idiotype and one public idiotype (cross-reactive idiotypes, CRI) were assigned, respectively to the third and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…However, there is a shared tetrapeptide in framework 2 (residues 36-39) that may explain the IdX we observed. Chen et al (19,20) using a synthetic peptide showed that the structural correlate of a human RF idiotype corresponds to a few amino acid residues on the light chain. The possible contribution of the light chain to IdX expression in our RF could be elucidated via immunoblotting analysis, hybrid molecules, and the preparation of monoclonal anti-Id antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a shared tetrapeptide in framework 2 (residues 36-39) that may explain the IdX we observed. Chen et al (19,20) using a synthetic peptide showed that the structural correlate of a human RF idiotype corresponds to a few amino acid residues on the light chain. The possible contribution of the light chain to IdX expression in our RF could be elucidated via immunoblotting analysis, hybrid molecules, and the preparation of monoclonal anti-Id antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Idiotypic determinants are autoantigens recognized by the immune system. The surface nature of idiotypic sequences is evidenced by anti-peptide antibodies interacting with intact immunoglobulin molecules (13)(14)(15)(16)(17)(18) and analysis of crystallographic structures of Fab fragments (19,20) and related proteins (21). Herein, a method is described that does not score surface-neutral substitutions in the analysis of evolutionary variability.…”
mentioning
confidence: 99%
“…-----------light-chain prototype sequence from position 42 to 95. This part of the gene includes two cross-reactive idiotypic determinants that were defined by antibodies against synthetic peptides corresponding to the second and third complementarity-determining regions (15,16,27). Fig.…”
Section: Resultsmentioning
confidence: 99%